Boganmeldelser - Garde, Peter; Kaspersson, Maria; Bech, Charlotte Mathiesen; Kramp, Peter; Langsted, Lars Bo; Ericsson, Kjersti; Larsson, Paul; Winge, Stig; Pedersen, René Dejbjerg (Nordisk Tidsskrift for Kriminalvidenskab, 2002)
Book reviews